HUBUNGAN ANTARA KEPUASAN KERJA DENGAN PRODUKTIVITAS KERJA PADA PEGAWAI BNN PROVINSI KALIMANTAN TIMUR - Rifdha Arvine Salsabila; Muslimin Nulipata; Tri Astuti (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Work productivity is an important indicator that reflects an organization's success in achieving its established objectives. One factor that is presumed to be associated with employees' work productivity is job satisfaction. This study aimed to examine the relationship between job satisfaction and work productivity among employees of the National Narcotics Agency (BNN) of East Kalimantan Province. This study employed a quantitative approach with a correlational research design. The study population consisted of 71 employees. The sample size was determined based on the Krejcie and Morgan Table, resulting in a minimum required sample of 61 employees. During the data collection process, data were successfully obtained from 64 employees who met the research criteria, namely active employees of BNN East Kalimantan Province who had worked for at least six months. Participants were selected using a purposive sampling technique. Data were collected using job satisfaction and work productivity scales that had met the required standards of validity and reliability. Data were analyzed using the Pearson Product-Moment Correlation technique with the assistance of IBM SPSS Statistics 32.0 for Windows. The results revealed a positive and statistically significant relationship between job satisfaction and work productivity, with a correlation coefficient of r = 0.658 and a significance value of p < 0.001. These findings indicate that employees with higher levels of job satisfaction tend to demonstrate higher levels of work productivity. Therefore, it can be concluded that there is a positive and significant relationship between job satisfaction and work productivity among employees of BNN East Kalimantan Province. ABSTRAK Produktivitas kerja merupakan salah satu indikator penting yang mencerminkan keberhasilan organisasi dalam mencapai tujuan yang telah ditetapkan. Salah satu faktor yang diduga berhubungan dengan produktivitas kerja pegawai adalah kepuasan kerja. Penelitian ini bertujuan untuk mengetahui hubungan antara kepuasan kerja dan produktivitas kerja pada pegawai Badan Narkotika Nasional (BNN) Provinsi Kalimantan Timur. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional. Populasi penelitian berjumlah 71 pegawai. Penentuan jumlah sampel mengacu pada Tabel Krejcie & Morgan, sehingga diperoleh jumlah sampel minimum sebanyak 61 pegawai. Pada pelaksanaan penelitian, data berhasil diperoleh dari 64 pegawai yang memenuhi kriteria penelitian, yaitu pegawai aktif BNN Provinsi Kalimantan Timur yang telah bekerja minimal 6 bulan, yang dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan menggunakan skala kepuasan kerja dan skala produktivitas kerja yang telah memenuhi persyaratan validitas dan reliabilitas. Analisis data dilakukan menggunakan teknik Korelasi Pearson Product Moment dengan bantuan IBM SPSS Statistics 32.0 for Windows. Hasil penelitian menunjukkan terdapat hubungan positif dan signifikan antara kepuasan kerja dan produktivitas kerja dengan nilai koefisien korelasi sebesar r = 0,658 dan nilai signifikansi p < 0,001. Temuan ini menunjukkan bahwa pegawai yang memiliki tingkat kepuasan kerja yang lebih tinggi cenderung memiliki tingkat produktivitas kerja yang lebih tinggi. Dengan demikian, terdapat hubungan positif dan signifikan antara kepuasan kerja dengan produktivitas kerja pada pegawai BNN Provinsi Kalimantan Timur.